Identifying Risk of Dementia Using Subjective Cognitive Decline (Scd) Instruments Among Elderly in Bandung, Indonesia - Juniarni, Lia; Pujianti, Risma; Ibrahim, Masdum (KnE Life Sciences, 2021)
Cognitive decline in the elderly is often referred to as dementia. Dementia is an effect of the aging process, which impacts the brain function. The subjective cognitive decline happens when a person’s cognitive perceptions experience decline but remain within parameters considered normal. A screening process for this condition is one of the efforts which can improve welfare services for the elderly. Subjective Cognitive Decline (SCD) is cognitive self-reports that assess subjective cognitive impairment abilities by prompting the recall of frequently experienced events. SCD has a double function, as an instrument for both early detection and the prevention of disease. This study aims to identify the risk of dementia using a Subjective Cognitive Decline (SCD) instrument. This research was conducted using a quantitative descriptive method with a cross-sectional approach. 187 elderly were taken as the sample by consecutive sampling methods, and data were analyzed using univariate analysis. This study showed that most of the respondents have a poor subjective cognitive decline, with 54.0%. The domains that have the most cognitive decline were the orientation with 78.1%, 76.5% of executive function, 68.4% of memory, and 59.4% of language. Demographic data associated with subjective cognitive decline showed poorly in female gender with 55.6%, age> 90 years with 55.3%, high school education with 70.4%, married status with 57.1%, and unemployed with 53.2%. This study concludes that the results of SCD with poor subjective cognitive decline have a risk of developing dementia. Keywords: Dementia, elderly, subjective cognitive decline